2007
DOI: 10.1055/s-2007-964929
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y Feeding Jejunostomy in Infants and Children

Abstract: Roux-en-Y jejunostomy (RYJ) permits enteral feeding in children unable to tolerate oral or intragastric feeds. It avoids many of the complications of nasojejunal and gastrojejunal tubes. Here we report our experience of intubated RYJ. By retrospective review of patient notes from 1998 - 2003, thirty-five children were identified. The median age was seven months (1 month - 16 years) and median follow-up was twenty-five months (1 - 55 months). There were no early postoperative complications or deaths. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 9 publications
(16 reference statements)
0
20
1
Order By: Relevance
“…Williams et al reported major complication rate of 37% [14] and Smith et al reported a major complication rate of 31% [15] with Roux-en-Y SJ. Taylor et al reported volvulus around Roux-en-Y SJ in 5 out of 25 patients (20% complication rate) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al reported major complication rate of 37% [14] and Smith et al reported a major complication rate of 31% [15] with Roux-en-Y SJ. Taylor et al reported volvulus around Roux-en-Y SJ in 5 out of 25 patients (20% complication rate) [16].…”
Section: Discussionmentioning
confidence: 99%
“…1 It seems to improve the nutritional status and to decrease complications associated with reflux and parenteral nutrition. 1,2 Unfortunately, the literature around this nutritional technique is sparse, especially based on a limited number of patients and studies, with lacking attention to benefits (weight gain, parental satisfaction, incidence of aspiration pneumonia). 3 Some surgical techniques have been described for the insertion of a feeding tube into the jejunum with no significant difference in terms of effectiveness and complications' rate.…”
Section: Introductionmentioning
confidence: 99%
“…3 Some surgical techniques have been described for the insertion of a feeding tube into the jejunum with no significant difference in terms of effectiveness and complications' rate. 1,2,4,5 Major complications have been studied in this small case series.…”
Section: Introductionmentioning
confidence: 99%
“…4 Several studies have shown that enteral feeding via a surgical jejunostomy is safe in pediatric and adult patients requiring post-pyloric feeding. [4][5][6][7] Many surgical jejunostomy techniques have been proposed since the first feeding jejunostomy was documented in the literature in 1858. 8 The most common techniques used by surgeons, whether open or laparoscopic, include the Witzel and the Roux-en-Y techniques, each having certain drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…4,10 While these complications may be avoided by using the Roux-en-Y technique, this procedure is of longer duration and requires the creation of a jejuno-jejunal anastomosis. 5 At our institution, we practice a tube jejunostomy technique that we feel is simple and may reduce the risk of bowel obstruction without the need of a sewn anastomosis. In addition, this method utilizes a feeding button which is easily replaceable and comfortable for the patient.…”
Section: Introductionmentioning
confidence: 99%